IOT Based Animal Health Monitoring System - Dr. Pradeep N. Fale,; Prof. Rachana Kurehekar,; Shraddha Marsattiwar,; Gayatri Nikame,; Kasturi Deogirkar,; Abhay Badwaik, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Animals are an essential part of the ecosystem, but their lives are now in danger. It is common for animals to roam freely in the farm, but if any accidents occur, such as physical injuries or illnesses, the farmer may not be able to determine the exact location of the animal. The Farm Animal Tracking System (FATS) project is a pioneering initiative designed to revolutionize livestock management within agricultural contexts by leveraging state-of-the-art tracking technologies. Animal Tracking System has implemented the use of GPS technology and the Internet of Things (IoT) to monitor and track farm animals, and sensors to collect real-time data on the location, behaviour, and vital signs of individual animals. This information is then processed through a centralized platform, providing farmers with valuable insights into herd dynamics, grazing patterns, and overall animal well-being. This paper outlines the application and use of these technologies. The primary goal of this project is to create a cost-effective solution to monitor a herd as a whole. The solution is an Internet of Things (IoT) based system, where some animals in the herd are equipped with GPS collars that are connected to the WiFi network.
Keywords: GPS; Internet of Things; WiFi; Farm Animal Tracking System